2014
DOI: 10.1002/ppul.23045
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in objectively assessed physical activity in asthmatic and non‐asthmatic children

Abstract: Unlike boys, girls with active asthma appear to be less active than their healthy peers, and this gender difference might explain the inconsistent evidence from previous reports on physical activity levels in asthmatic children. Further studies are needed to confirm the gender interaction in the childhood asthma-physical activity relation and the implications on current guidelines for physical exercise prescriptions in asthmatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 39 publications
4
27
1
Order By: Relevance
“…Like others, [6] , [16] we found sex-specific associations between asthma, rhinitis and PA. However, while Groth et al (2016) [6] and the current study found that asthma was associated with PA only in boys, Yiallouros et al (2015)[16] found an effect only in girls, while Sugimoto et al[5] found that rhinitis was associated with lower PA only in boys.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Like others, [6] , [16] we found sex-specific associations between asthma, rhinitis and PA. However, while Groth et al (2016) [6] and the current study found that asthma was associated with PA only in boys, Yiallouros et al (2015)[16] found an effect only in girls, while Sugimoto et al[5] found that rhinitis was associated with lower PA only in boys.…”
Section: Discussionsupporting
confidence: 87%
“…However, while Groth et al (2016) [6] and the current study found that asthma was associated with PA only in boys, Yiallouros et al (2015)[16] found an effect only in girls, while Sugimoto et al[5] found that rhinitis was associated with lower PA only in boys. This heterogeneity may be explained by the known gender differences in prevalence, symptoms, and progression of asthma [39–42] and/or cultural differences in acceptability of sport [43, 44] especially for girls or children with asthma.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…6 7 Systematic reviews have suggested that children with asthma engage in less physical activity than children who do not have asthma, and these differences may be more marked for girls than boys. [8][9][10] In addition, a recent systematic review of epidemiological studies has shown that children with low levels of physical activity are at up to 35% increased risk of new onset asthma and/or wheezing. 11 The same review also reported that more than 50% of the cross-sectional studies reported positive associations between low physical activity and childhood asthma.…”
Section: Introductionmentioning
confidence: 99%